Edukasi Bisnis Usaha Mikro Kecil dan Menengah (UMKM) Yang Berwawasan Hukum di Kota Pekanbaru - Admiral Admiral; Imam Riauan; Suparto Suparto; Puti Mayang Seruni; Monika Melina; Naurah Dwirengganis Riata Putri (I-Com: Indonesian Community Journal, 2024)
Legal issues in business are a troubling issue for business people. This is due to several reasons, including ignorance regarding legal entity forms, lack of knowledge in the field of contract law, problems in the field of business digitalization, lack of knowledge regarding consumer protection, lack of knowledge regarding resolving business disputes through negotiation and mediation. This activity has never been held in pekanbaru kota district. The aim of this activity is so small business owner can learn about business law and alternative dispute resolution that can be applied in running a business. The method of this activity consists of the material creation phase, direct lectures and presentation, counseling with legal experts, and evaluation. The results of this activity are in the form of increased insight and knowledge of small business owners regarding legal issues. Another benefit of this activity is that small business owners also get relationships and access to consultations with legal experts.